Investigation of Production Possibility of Medical Isotope 155Tb on Cyclotron C18/18 - Avetisyan, R. V.; Barseghyan, A. G.; Gharibyan, Yu. H.; Gyurjinyan, A. V.; Kerobyan, I. A.; Mkrtchyan, H. A.; Petrosyan, A. Yu (Journal of contemporary physics, 2024)
The results of the studies on the production of 155 Tb isotope, which is used in theranostic applications for oncological diseases, utilizing the proton beam of the medical cyclotron C18/18 are presented. The measurements of the induced activity were carried out using the activation method, followed by spectrometric analysis. Natural gadolinium was used as the main target. Excitation functions were calculated for the nat Gd( p , xn ) 155 Tb reactions using TALYS 1.96 and EMPIRE 3.2 theoretical nuclear codes. The measured cross-section values were compared with the results of the theoretical calculations as well as with the experimental data from other works. The experimental value of the integral activity of the radionuclide 155 Tb was compared to the results obtained with the TALYS 1.96 code and with early published data.